Metallization of Carbon Fibers by Double and Triple Copper Composition - Sirenko, H.O.; Skladanyuk, M.B.; Soltys, L.M. (Physics and Chemistry of Solid State, 2015)
The theoretical foundations of physics and chemistry and application technology of single- and double-layer coating based on Cu0+Cu2O, Ni0+P, Pb0 on the surface of carbonated fibers have been reviewed. The changes of surface layers crystal structure of carbon fibres in the course of copper-plating have been investigated. The metallic coating process using modified formaldehyde and zinc technology was realized. It is established that copper content in copper – copper oxide increases when using two-layer alternately modified formaldehyde and zinc methods.